Disclosure of Important Issues in Audit Reports: First Year of Implementation - Petropoulos, Georgios; Tsipouridou, Maria; Boskou, Georgia; Spathis, Charalambos (International Conference on Business and Economics - Hellenic Open University, 2023)
The aim of this study is to explore the new International Standard on Audit (ISA) 701 “Communicating Key Audit Matters in the Independent Auditor´s Report”. More specifically, we examine Key Audit Matters (KAMs) in the first year of implementation in Greece, in 2017. We content analyze the audit reports to investigate the number and type of KAMs that are identified and disclosed by industry and by type of audit firm (i.e. Big-4, Crowe-Sol, Grant Thornton, and others). We hand-collect data from 153 audit reports of companies listed on the Athens Stock Exchange (ASE). Moreover, an empirical analysis is carried out to examine whether the size of the company being audited, and the type of the audit firm, affect the number of KAMs. Οur results show that the number of KAMs is positively related to the size and leverage of the audited company, as well as the tenure of the audit firm. Key words: Key Audit Matters, ISA 700, ISA 701 JEL Classification: M41, M42, G38